2019
DOI: 10.1530/eje-19-0017
|View full text |Cite
|
Sign up to set email alerts
|

The brown fat-secreted adipokine neuregulin 4 is decreased in human and murine chronic kidney disease

Abstract: Objective Neuregulin 4 (NRG4) has recently been introduced as a novel brown adipose tissue (BAT)-secreted adipokine with beneficial metabolic effects in mice. However, regulation of Nrg4 in end-stage kidney disease (ESKD) and type 2 diabetes mellitus (T2DM) has not been elucidated, so far. Design/methods Serum NRG4 levels were quantified by ELISA in 60 subjects with ESKD on chronic hemodialysis as compared to 60 subjects with an estimated glomerular filtration rate >50 mL/min/1.73 m2 in a cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Surprisingly, we found no significant differences in the prevalence of DN and DR, and DN-related markers across quartiles of circulating Nrg4 and circulating Nrg4 was also not associated with the prevalence of DN and DR, and DN-related markers, suggesting that circulating Nrg4 levels may not involve in the pathogenesis of diabetic microvascular complications other than DPN, and the three diabetic microvascular complications might have other different pathogenetic mechanisms. Our data coincide with a previous report showing that there was no significant difference in serum Nrg4 level between T2DM patients with and without DR [35], but are not consistent with the studies performed by Kralisch et al and Zahid Kocak et al [35,42]. Kralisch et al found that circulating Nrg4 was significantly lower in patients with end-stage kidney disease on maintenance renal replacement therapy treatment compared to subjects with an eGFR > 50 ml/min/1.73 m 2 and independently associated with a preserved renal function and mRNA expression of Nrg4 is reduced in adipose tissue depots of mice with diabetic kidney disease as compared to nondiabetic control mice [42].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Surprisingly, we found no significant differences in the prevalence of DN and DR, and DN-related markers across quartiles of circulating Nrg4 and circulating Nrg4 was also not associated with the prevalence of DN and DR, and DN-related markers, suggesting that circulating Nrg4 levels may not involve in the pathogenesis of diabetic microvascular complications other than DPN, and the three diabetic microvascular complications might have other different pathogenetic mechanisms. Our data coincide with a previous report showing that there was no significant difference in serum Nrg4 level between T2DM patients with and without DR [35], but are not consistent with the studies performed by Kralisch et al and Zahid Kocak et al [35,42]. Kralisch et al found that circulating Nrg4 was significantly lower in patients with end-stage kidney disease on maintenance renal replacement therapy treatment compared to subjects with an eGFR > 50 ml/min/1.73 m 2 and independently associated with a preserved renal function and mRNA expression of Nrg4 is reduced in adipose tissue depots of mice with diabetic kidney disease as compared to nondiabetic control mice [42].…”
Section: Discussionsupporting
confidence: 71%
“…Our data coincide with a previous report showing that there was no significant difference in serum Nrg4 level between T2DM patients with and without DR [35], but are not consistent with the studies performed by Kralisch et al and Zahid Kocak et al [35,42]. Kralisch et al found that circulating Nrg4 was significantly lower in patients with end-stage kidney disease on maintenance renal replacement therapy treatment compared to subjects with an eGFR > 50 ml/min/1.73 m 2 and independently associated with a preserved renal function and mRNA expression of Nrg4 is reduced in adipose tissue depots of mice with diabetic kidney disease as compared to nondiabetic control mice [42]. Similarly, Zahid Kocak and collaborators demonstrted that serum Nrg4 significantly reduced in T2DM patients with DN, and serum Nrg4 was negatively associated with microalbuminuria [35].…”
Section: Discussionsupporting
confidence: 71%
“…Although Nrg4, an ErbB4‐specific ligand, is expressed in different organs and was first identified as a neuregulin family protein enriched in the pancreas, subsequent studies revealed that brown adipose tissue (BAT) expresses the highest levels of Nrg4 . Nrg4, a recently identified adipokine, is a member of the epidermal growth factor (EGF) family of extracellular protein ligands that functions in an autocrine/paracrine or endocrine manner via a proteolytic liberation of the EGF‐like domain . It is a novel adipose tissue–enriched endocrine factor involved in the modulation of glucose and lipid metabolism and energy homeostasis .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we related Pro-NT levels to mortality in 163 ESKD patients. Moreover, we investigated NT regulation in two mouse models of diabetic kidney disease (DKD) vs two groups of non-diabetic control mice (18).…”
Section: Introductionmentioning
confidence: 99%